Drug Dose Adjustment in Dialysis Patients Admitted in Clinics Other Than Internal Medicine. (January 2016) - Solak, Yalcin; Biyik, Zeynep; Gaipov, Abduzhappar; Kayrak, Mehmet; Ciray, Hilal; Cizmecioglu, Ahmet; Tonbul, Halil Zeki; Turk, Suleyman
Abstract : Many drugs that are administered during hospitalization are metabolized or excreted through kidneys, consequently require dosage adjustment. We aimed to investigate inappropriate prescription of drugs requiring renal dose adjustment (RDA) in various surgical and medical inpatient clinics. We retrospectively determined dialysis patients hospitalized between January 2007 and December 2010. Inpatient clinics, including cardiology, pulmonary medicine, neurology, infectious diseases (medical clinics) and cardiovascular surgery, orthopedics, general surgery, obstetrics and gynecology, and neurosurgery (surgical clinics), were screened via electronic database. Total and RDA medications were determined. RDA drugs correctly adjusted to creatinine clearance were labeled as RDA-A (appropriate), otherwise as RDA-I (inappropriate). Renal doses of RDA medications were based on the "American College of Physicians Drug Prescribing in Renal Failure, fifth Edition." Two hundred seventeen hospitalization records of 172 dialysis patients (92 men and 80 women) were included in the analysis. Mean age of patients was 59.4 ± 14.6 years, and the mean hospitalization duration was 8.5 ± 7.8 days. In total, 247 (84.3%, percentage in drugs requiring dose adjustment) and 175 (46.2%) drugs have been inadequately dosed in surgical and medical clinics, respectively. The percentage of patients to whom at least 1 RDA-I drug was ordered was 92% and 91.4% for surgical and medical clinics, respectively ( P > 0.05). Nephrology consultation numbers were 8 (7.1%) in surgical and 32 (30.4%) in medical clinics. The most common RDA-I drugs were aspirin and famotidine. A significant portion of RDA drugs was ordered inappropriately both in surgical and medical clinics. Nephrology consultation rate was very low. Measures to increase physician awareness are required to improve results.